Pharmacovigilance Strategy for COVID-19 Vaccine Information Management and Utilization among Health Information Managers in Kwara State, Nigeria - Salman, Abdulsalam Abiodun; Jacob, Priscilla Ayooluwa; Idris, Saleh; Bako, Abdullateef (Universitas Komputer Indonesia, 2023)
Diversified opinions on the efficacy of COVID-19 vaccine have necessitated investigation on the pharmacovigilance strategies used to manage COVID-19 vaccine information and perception of health information managers. Narrative research design was adopted while structured interview was used to collect data from respondents and qualitative data analysis technique was employed. Total enumeration was adopted to gather data from eight (8) purposively selected health information managers in the Ministry of Health, Kwara State. The study revealed that majority of the respondents are aware of pharmacovigilance and COVID-19 vaccine information are managed through WHO guideline. Virtual meetings, emergency preparedness and response are some opportunities provided for COVID-19 vaccines information management. Vaccine hesitancy, non-compliance to usage-regulations, misinformation and overwhelmed facility were identified as challenges with acceptance of the vaccine. The study thus recommended that pharmacovigilance be enhanced among health information managers using advance information management technology.